1991
DOI: 10.1152/ajpendo.1991.260.2.e262
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of IGF-I and insulin in spontaneously diabetic BB/w rats

Abstract: To examine the influence of insulin-dependent diabetes on the metabolic response to insulin-like growth factor I (IGF-I), awake chronically catheterized diabetic and nondiabetic BB/w rats received IGF-I (5 micrograms.kg-1.min-1) or insulin (2 mU.kg-1.min-1) for 2 h while maintaining euglycemia. In nondiabetic rats, IGF-I and insulin produced similar twofold increases in glucose uptake, but insulin was more effective in reducing hepatic glucose production (90 +/- 15 vs. 5 +/- 11%; P less than 0.001) and beta-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
22
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 31 publications
11
22
0
Order By: Relevance
“…In the normal rats, the ratio of ED85 of potency of insulin to IGF-I on a molar basis was 1/79. In contrast, the ratio was increased to 1/24 in streptozotocin-diabetic rats, in agreement with the earlier study by Jacob et al [18] that in BB/w rats IGF-I infusion showed more suppression of hepatic glucose production than non-diabetic rats. The reason for the rather increased sensitivity of hepatic glucose output to IGF-I is not clearly explained.…”
Section: Suppressive Effect Of Igf-i and Insulin On Hepatic Glucose Osupporting
confidence: 92%
See 1 more Smart Citation
“…In the normal rats, the ratio of ED85 of potency of insulin to IGF-I on a molar basis was 1/79. In contrast, the ratio was increased to 1/24 in streptozotocin-diabetic rats, in agreement with the earlier study by Jacob et al [18] that in BB/w rats IGF-I infusion showed more suppression of hepatic glucose production than non-diabetic rats. The reason for the rather increased sensitivity of hepatic glucose output to IGF-I is not clearly explained.…”
Section: Suppressive Effect Of Igf-i and Insulin On Hepatic Glucose Osupporting
confidence: 92%
“…The maximum effects of insulin and IGF-I were identically decreased to about 70% of that of normal rats. This result was in accord with an earlier report by Jacob et al [18] on spontaneously diabetic BB/w rats, although controversial results of no IGF-I resistance in partially pancreatectomized rats were reported by Rosetti et al [19]. Sowell et al [20] reported the interesting observation that rat skeletal muscle treated with phenylarsine oxide (PAO), an agent believed to block insulin stimulated glucose transport at a postreceptor level, was resistant also to IGF-I.…”
Section: Suppressive Effect Of Igf-i and Insulin On Hepatic Glucose Osupporting
confidence: 88%
“…In a previous study, lipid metabolism was investigated in mouse monocytes after incubation with [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]oleate (33). Of the radioactivity associated with lipid, 80% of oleate was shown to be incorporated into triglycerides, 18% was incorporated into phospholipids, and 2% was recovered as non-esterified fatty acids.…”
Section: Effects Of Igf-i On Glut Isoformsmentioning
confidence: 99%
“…However, in contrast to insulin, IGF-I is ineffective in suppressing hepatic glucose production (6)(7)(8) and has a preferential effect to increase the rates of glycolysis in tissues such as muscle (5). The effects of IGF-I on glucose disposal in hyperthyroidism have never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was associated with enhanced glucose utilization by skeletal muscle [4] and indeed was reflected in increased hexose uptake by muscles in vivo [5]. This metabolic effect of IGF-I is specific and independent of actions on the insulin receptor, and it has been proposed that IGF-I stimulation of glucose uptake can bypass insulin resistance in certain animal models of diabetes [3,6]. The molecular mechanism underlying such stimulation of glucose influx into muscle is unknown.…”
mentioning
confidence: 99%